Exploring risk factors and transmission dynamics of Hepatitis B infection among Indian families: Implications and perspective - Shreyasi Athalye; Naveen Khargekar; Shailesh Shinde; Tejashwini Parmar; Shreya Chavan; Ganeshmoorthy Swamidurai; Vaishali Pujari; Priyanka Panale; Priyanka Koli; Aruna Shankarkumar; Anindita Banerjee (Journal of Infection and Public Health, 2023)
Introduction: Hepatitis B virus (HBV) is global health problem. Family members of HBV infected people are considered as high-risk groups due to frequent household transmission of HBV among contacts of HBsAg carriers. The present study aimed to investigate the intrafamilial transmission of HBV among family members of HBV-infected persons and to identify the risk factors for viral transmission in these setting. Methods: 361 index cases and their 1083 family contacts were tested for markers of Hepatitis B, viz. HBsAg and HBcAb using commercial ELISA. The demographic details and risk factors for acquiring HBV infection among the family members were recorded using a structured questionnaire. Results: The median (IQR) age of index cases and family members was 37 (27 − 48) and 26 (14 − 38) years, respectively. Among the screened family members, 9.23% (n = 100) members were positive for HBsAg and 32.75% (n = 355) were positive for HBcAb. At least one member of the family was affected in 229/361 (63.43%) index cases. Significantly lower percent of household contacts (9.23%, n = 100)were vaccinated against HBV.HBV transmission risk was significantly higher in families with more than four members(p < 0.0001). Multinomial logistics regression analysis for familial risk factors for transmission of HBV such asclose contact with carrier (aOR overt: 1.172, aOR occult: 1.173), sharing of bed/bedding (aOR overt: 1.258, aOR occult:1.264), personal hygiene items (aOR overt:1.260, aOR occult: 1.451), and eating in common utensils (aOR overt: 2.182, aOR occult: 1.307)were significantly associated with the transmission of HBV (p < 0.05). Discussion: Close contact with carrier, sharing of bed/bedding or personal hygiene items and eating in common utensils were significantly associated with the transmission of HBV. Increasing awareness about Hepatitis B infection and vaccination of family members in close contact with carrier is essential to prevent Hepatitis B transmission.